RETRACTED: Improving the standardization of wagon standby time at the sorting station - Butunov Dilmurod; Mukhammadiev Komil; Abdukodirov Sardor; Buriyev Shuhrat; Toxtakxodjaev Mafirat (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001